PROTEUS VULGARIS: Proving and Clinical Use in Paediatrics - Dominici, Gustavo (Homœopathic Links, 2018)
Introduction The Homeopathic School of Verona in Italy organises Hahnemannian provings for experimental and educational purposes. In 2013 Proteus vulgaris was tested. The results of the proving and the data in the literature allowed the clinical use of the remedy.Methods Participants: 15 experienced provers, 10 expert supervisors, 1 coordinator, 1 director. Potency tested: 200K; 3 placebos or blank (20%). It was a triple-blind proving. Observation time: 30 days; periodical checks up to 1 year.Findings The mental symptoms of the proving of Proteus vulgaris are characterised by extreme violence in any event. There is restlessness, uncontrollable mobility; it is polemic, hard and aggressive; there is destructive criticism. It breaks consolidated relationships. There is insomnia. The most affected systems are gastrointestinal and urinary tracts. Finger joints are affected. Headaches also occur. The symptoms in the literature complete the pathogenesis–clinical picture and allow the prescription.Differential diagnosis: Iodum, Hyoscyamus, Medorrhinum, Mercurius solubilis and corrosivus, Staphisagria, Syphilinum, Tarentula. The author shows two clinical cases of children: the first with many behavioural problems and mild autism; the second with attention deficit hyperactivity disorder (ADHD) syndrome.Conclusions The proving is the best method for defining the pathogenesis of a new substance. The results must be completed with the literature data. Proteus is a homeopathic remedy with very intense and characteristic symptoms and can be used successfully in clinical practice, particularly in children with behavioural disorders including ADHD syndrome.
Keywords: Behavioural Disorders; ADHD; Proteus vulgaris